Introductions and Scene-setting - Somogyi, Dalma (2018)
The presentation Global Policy Frameworks And Their Implications For Metrics is by Dalma Somogyi, Manager of Climate Smart Agriculture project for WBCSD. Presented at the WBCSD Climate Smart Agriculture workshop at the University of Vermont, Burlington, VT on 28 March 2018.